Old age allowance program for the socio-economic development and social security of older people: a quantitative study in climate-vulnerable areas of Bangladesh - Md. Golam Azam; Md. Abdul Mazid; Saidur Rahman (Indonesian Journal of Community Services, 2026)
The old age allowance program has been continuing in Bangladesh for the last two and a half decades, contributing to socioeconomic development and social security of elderly populations, or whether the program is contributing according to the needs of the elderly population is the subject of evaluation.  The objective of the study is to evaluate the old age allowance program for the socioeconomic development and social security of the elderly population. It was conducted in 24 villages across eight (08) climate-vulnerable districts of Bangladesh using quantitative research methods, and with a quantitative survey employed for field-level data collection. The study findings reveal that the program contributes positively to the overall socio-economic development of the elderly population especially in economic development (93%), social development (85%), fulfilling nutritional demands (52%), increasing mental peace (99%), helps to be physically healthy (94%), supports as an alternative source of income (88%), and reduces the dependency on others (84%) of the elderly persons. Although the program contributes significantly to the economic, social, and psychological welfare of elderly beneficiaries in climate-vulnerable areas of Bangladesh, its ability to ensure genuine social security and adequate nutrition remains inadequate. However, where only 61% of respondents remark on enhanced social security, the allowance sum scarcely covers basic human needs. Pragmatic policy reforms, such as increasing the allowance from BDT 600 to BDT 1500; revising the age of eligibility to 55 for women and 60 for men; introducing a biometric allowance distribution system; and establishing a dedicated banking system, are required to boost program efficiency.